2015
DOI: 10.1242/dmm.018960
|View full text |Cite
|
Sign up to set email alerts
|

Modeling autosomal recessive cutis laxa type 1C (ARCL1C) in mice reveals distinct functions of Ltbp-4 isoforms

Abstract: Recent studies have revealed an important role for LTBP-4 in elastogenesis. Its mutational inactivation in humans causes autosomal recessive cutis laxa type 1C (ARCL1C), which is a severe disorder caused by defects of the elastic fiber network. Although the human gene involved in ARCL1C has been discovered based on similar elastic fiber abnormalities exhibited by mice lacking the short Ltbp-4 isoform (Ltbp4S−/−), the murine phenotype does not replicate ARCL1C. We therefore inactivated both Ltbp-4 isoforms in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 49 publications
2
72
0
Order By: Relevance
“…It has been demonstrated that Ltbp-4 isoforms functionally interact with fibulin-5 (Bultmann-Mellin et al, 2015; Noda et al, 2013). The fibrillar structure of fibulin-5 appeared normal in aortas of WT and Fibulin-4 R/R mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that Ltbp-4 isoforms functionally interact with fibulin-5 (Bultmann-Mellin et al, 2015; Noda et al, 2013). The fibrillar structure of fibulin-5 appeared normal in aortas of WT and Fibulin-4 R/R mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3" type="url"/>). This was most likely causative for the higher postnatal mortality of Ltbp4S −/− ; Fibulin-4 R/R mice compared to Ltbp4 −/− mice (Bultmann-Mellin et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations